Von der internationalen zur transnationalen Politik. Dargestellt am Beispiel der europäischen (Kern-)Region Saar-Lor-Lux-Trier/Westpfalz ; Entwicklung eines (3+1)-Ebenen-Modells interregionaler Zusammenarbeit - Sinewe, Werner (Lang, 1998)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage/2006/01/01/file_465/1127453.pdf
Keywords: Europäische Integration; Grenzüberschreitende Kooperation; Regionalpolitik; Saar-Lor-Lux

Saar-Lor-Lux. Die Bedeutung der lokalen grenzüberschreitenden Kooperation für den europäischen Integrationsprozeß - Schulz, Christian (Europa Regional, 1997)
Abstract: „The intermunicipal, cross-border co-operation in the European border regions has experienced a dynamic thrust of development in the last few years. This was facilitated by the changes in the political, legal and financial framework conditions, to which the community initiative INTERREG provided a considerable contribution. An additional factor in the Saar-Lor-Lux region is that subunits form in the actual border regions within the generously measured, regional work areas of the interregional co-operation, characterised by a fairy homogenous regional structure. Using three case examples, it is demonstrated that cross-border organisation structures have developed within these small regions on a municipal level. These are being institutionalised more and more. Using the regional development model of the network of cities, which is being discussed with regards to its cross-border applicability, we can in this context speak of local co-operation networks. In the case of the Agglomération Transfrontalière du Pôle Européen de Développement (PED) in the Belgian-French-Luxembourg state triangle, the participating local authority districts and government authorities have joined together to form an association and maintain a joint Observatoire de l'Urbanisme, responsible among other things since 1996 for the registration and processing of regional data as well as for the development of land use concepts. The M eeting of Mayors and/or the Ronde des Trois Frontières, responsible for the development of tourism in the German-French-Luxembourg Moselle Valley, are considerably less formal network structures. The co-operation between the border local authority districts was institutionalised in the Saar-Rosselle region in the form of the Intermunicipal Association for Work. The latter maintains a co-operation office with the Saarbrücken city association, principally responsible for co-ordination tasks with regards to current and developing, cross-border projects. Despite the depicted structural and legal impediments, an increased institutionalisation of the co-operations can be observed; this goes hand in hand with a topical diversification, which deincreasingly covers subject areas which have been avoided up until now because of the potential conflicts found therein, as demonstrated by the example of the joint commercial area development in the case of the Agglomération du PED. These observed case examples deal with increasingly integrated core regions within a border region which can provide important impulses for the interregional and also international dialogue. At the same time, practical measures were implemented on this level, which are perceived by the local population in day to day life and therefore have greater identity-forming effects. In this context, these measures can provide an essential or even exemplary contribution to overcoming the interior borders of the EU. These approaches can be understood as being a basis for integration "from the bottom up" which make a greater sustainability and acceptance in the various sectors of day to day living more probable, unlike the top-down forces which dominate the realisation of the European common market or the currency union.“
Keywords: Europäische Integration; Finanzierung; Grenzüberschreitende Kooperation; Netzwerk; Recht; Regionalentwicklung; Saar-Lor-Lux; Stadt; Wirtschaftsförderung